2010
DOI: 10.1038/hr.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the risk profile and male predominance in silent brain infarction in community-dwelling elderly subjects: the Sefuri brain MRI study

Abstract: Although brain infarction is more common in men, the male predominance of silent brain infarction (SBI) was inconsistent in the earlier studies. This study was to examine the relationship between sex differences in the risk profile and SBI. We conducted a population-based, cross-sectional analysis of cardiovascular risk factors and SBI on MRI. We asked all the female participants about the age at natural menopause and parity. SBI was detected in 77 (11.3%) of 680 participants (266 men and 414 women) with a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…In only three [33,39,48] out of 15 studies in which an association was sought has tobacco been identified as a statistically significant risk factor for SBI [see Additional file 4: Table S3]. Of particular note is that, although the Rotterdam Scan Study identified a statistically significant increase in clinically apparent stroke (OR: 3.1; 95% CI: 0.6, 1.5), no such association was demonstrated for SBI even among the heaviest smokers with ≥20 pack year histories (OR: 1.0; 95% CI: 0.6, 1.5) [38].…”
Section: Lifestyle Factors Tobaccomentioning
confidence: 99%
“…In only three [33,39,48] out of 15 studies in which an association was sought has tobacco been identified as a statistically significant risk factor for SBI [see Additional file 4: Table S3]. Of particular note is that, although the Rotterdam Scan Study identified a statistically significant increase in clinically apparent stroke (OR: 3.1; 95% CI: 0.6, 1.5), no such association was demonstrated for SBI even among the heaviest smokers with ≥20 pack year histories (OR: 1.0; 95% CI: 0.6, 1.5) [38].…”
Section: Lifestyle Factors Tobaccomentioning
confidence: 99%
“…We have reported a male predominance in SBI, which was largely due to a higher prevalence of alcohol intake and smoking in men than women in our population. 28 In the same context, frontal lobe dysfunction was related to male sex in model 1 but not in the final multivariate model that included MRI findings (model 2). Subcortical vascular disease and DWMLs seen in elderly subjects were associated with cognitive impairment or dementia, depression, apathy and gait disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…SBI appeared as low signal intensities on T1-weighted images, and their size was X5 mm as previously described. 28 We differentiated enlarged perivascular spaces from SBI based on their location, The logarithmically transformed MST scores and eGFR were distributed near normally.…”
Section: Assessment Of Mri Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Hypertension Research, Takashima et al 12 focus on the gender difference in SBI incidence among Japanese people with a population-based, cross-sectional analysis. The study comprised 266 men and 414 women with a mean age of 64.5 years.…”
mentioning
confidence: 99%